2014
DOI: 10.1007/s40268-014-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen Sodium Is Absorbed Faster than Standard Ibuprofen Tablets: Results of Two Open-Label, Randomized, Crossover Pharmacokinetic Studies

Abstract: BackgroundA novel ibuprofen (IBU) formulation, Advil® Film-Coated Tablets (IBUNa), was developed.ObjectivePharmacokinetic comparison of IBUNa versus other IBU formulations.Study DesignTwo randomized, single-dose, open-label, five-way crossover pharmacokinetic studies.SettingInpatient research clinic.SubjectsSeventy-one healthy adult volunteers.InterventionStudy 1: In three periods, fasted subjects received 400-mg IBU dose equivalents as IBUNa 2 × 256 mg, Advil® Liqui-Gels® (IBULG) 2 × 200 mg, and Motrin® IB (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…Comparable results with regards to key PK parameters reflecting faster absorption of ibuprofen salts including ibuprofen sodium and ibuprofen lysinate under fasted conditions were published by Legg and colleagues . As with the data presented here, the higher C max for the salts that are absorbed fastest (ibuprofen sodium and lysinate) compared with the standard formulation (ibuprofen acid) observed under fasted conditions disappeared if the study medication was administered within 20 minutes of a standardized high‐fat breakfast.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Comparable results with regards to key PK parameters reflecting faster absorption of ibuprofen salts including ibuprofen sodium and ibuprofen lysinate under fasted conditions were published by Legg and colleagues . As with the data presented here, the higher C max for the salts that are absorbed fastest (ibuprofen sodium and lysinate) compared with the standard formulation (ibuprofen acid) observed under fasted conditions disappeared if the study medication was administered within 20 minutes of a standardized high‐fat breakfast.…”
Section: Discussionsupporting
confidence: 83%
“…As with the data presented here, the higher C max for the salts that are absorbed fastest (ibuprofen sodium and lysinate) compared with the standard formulation (ibuprofen acid) observed under fasted conditions disappeared if the study medication was administered within 20 minutes of a standardized high‐fat breakfast. Also, the pronounced difference between faster‐absorbed salts and standard, with regard to median t max in minutes, diminished considerably under fed conditions …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is consistent with partial AUC findings, which showed ibuprofen 600 mg IR/ER had a higher AUC 0-4 (76.8 μg·h/mL) compared with that for ibuprofen 200 mg IR (42.2 μg·h/mL). 7 In contrast to the partial AUC 0-4 observations above, there were no significant differences in AUC 4-8 between ibuprofen 600 mg IR/ER and ibuprofen 200 mg IR × 3, whereas the AUC 8-12 for ibuprofen 600 mg IR/ER was significantly lower than that found for ibuprofen 200 mg IR every 4 hours (P < .001). The overall extent of ibuprofen absorption was bioequivalent for ibuprofen 600 mg IR/ER under fasted and fed conditions for all AUC measures.…”
Section: Discussionmentioning
confidence: 55%
“…[5][6][7] Geisslinger and colleagues found that T max was prolonged in the presence of food, where median T max was prolonged by 0.66 hours for ibuprofen free acid and by 0.63 hours for ibuprofen lysinate versus when these 2 respective formulations were administered in the fasted state. However, the overall fasted C max for ibuprofen 600 mg IR/ER was 69% higher than the C max 0-4 (ie, C max after the first, fasted dose) for ibuprofen IR.…”
Section: Discussionmentioning
confidence: 99%